2020
DOI: 10.1128/jvi.01066-20
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Swine Origin Influenza A(H1N1) Pandemic 2009 Viruses in Humans following Zoonotic Transmission

Abstract: Human-to-swine transmission of seasonal influenza viruses has led to sustained human-like influenza viruses circulating in the United States swine population. While some reverse zoonotic-origin viruses adapt and become enzootic in swine, nascent reverse zoonoses may result in virus detections that are difficult to classify as ‘swine-origin’ or ‘human-origin’ due to the genetic similarity of circulating viruses. This is the case for human-origin influenza A(H1N1) pandemic 2009 (pdm09) viruses detected in pigs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
12
2
Order By: Relevance
“…Genotypic analysis revealed that both viruses had genes derived from A(H1N1)pdm09 virus; PA, NP, and MP in case of OH/24 and PB2, PB1, NP, and MP in case of Alberta/1 ( Figure 1 ). A/Michigan/288/2019 (MI/288) A(H1N1)v virus was previously phylogenetically classified as alpha lineage (1A.3.3.2) [ 15 ], while the HA and NA of this virus clustered with contemporary human A(H1N1)pdm09 viruses (clade 6B.1A) and swine IAVs from the USA; all of the internal protein coding vRNAs were similar to swine viruses circulating in the USA ( Figure 1 ). The PB1 and PA genes clustered with those of the A/swine/Texas/4199-2/1998 virus used in a commercial, live-attenuated swine vaccine in the USA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotypic analysis revealed that both viruses had genes derived from A(H1N1)pdm09 virus; PA, NP, and MP in case of OH/24 and PB2, PB1, NP, and MP in case of Alberta/1 ( Figure 1 ). A/Michigan/288/2019 (MI/288) A(H1N1)v virus was previously phylogenetically classified as alpha lineage (1A.3.3.2) [ 15 ], while the HA and NA of this virus clustered with contemporary human A(H1N1)pdm09 viruses (clade 6B.1A) and swine IAVs from the USA; all of the internal protein coding vRNAs were similar to swine viruses circulating in the USA ( Figure 1 ). The PB1 and PA genes clustered with those of the A/swine/Texas/4199-2/1998 virus used in a commercial, live-attenuated swine vaccine in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…Ferret immune sera were harvested 14 days post intranasal inoculation with 6 log 10 50% egg infectious dose (EID 50 ) of virus. Two-way hemagglutination inhibition (HI) assay was used to assess cross-reactivity between different virus strains and pooled human sera (with human subject research approval [ 14 ]) as previously described [ 15 ]. Briefly, each serum sample was treated at a 1:4 dilution with receptor-destroying enzyme (RDE, Denka Seiken) for 18 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Influenza A virus (IAV) infection causes severe respiratory symptoms and persistent morbidity as well as mortality during annual seasonal or pandemic outbreaks, resulting in a severe threat to public health and safety, and even huge economic burden (1). Over the past decade, influenza outbreaks and pandemics have been caused by different subtypes of IAV, including H1N1, H3N2, swine-origin H1N1, and highly pathogenic avian influenza viruses (2)(3)(4), suggesting that the deeper biologic and epidemiologic mechanisms should be revealed to confidently and accurately predict the next influenza outbreak. Accumulative evidence has shown that IAV is capable of eliciting cellular immune response thought changing the expression of multiple genes in diverse types of cells, which in turn inhibit IAV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the 20th century, zoonotic spillover events have given rise to the generation of multiple, well-documented pandemic IAVs [3][4][5]. Intensification of animal husbandry, increasing encroachment into wildlife habitats for agricultural use, and increased connectivity of livestock populations through (transboundary) trade, created favorable conditions that are associated with the establishment of new IAV lineages in these reservoirs but also created new interfaces for human infections [6][7][8][9][10][11]. Some examples include the 2009 pandemic swine influenza virus [12] and an increasing number of reported zoonotic spillover infections with avian IAVs (AIVs) from poultry [13,14].…”
Section: Introductionmentioning
confidence: 99%